Human Capital Development, ISO 22000 Adoption, and Performance Sustainability of Small and Medium Enterprises in the Food Sector: An Integrated Theoretical and Descriptive Analysis - Dr. Elias Mwangi Kilonzo (Frontline Social Sciences and History Journal, 2025)
Small and medium enterprises play a foundational role in national economies through employment creation, innovation, income generation, and social stability. In developing and emerging economies, SMEs constitute the largest proportion of registered businesses and are especially dominant in the food sector, where they directly influence public health, consumer trust, and economic resilience. Despite their importance, food-based SMEs face persistent challenges related to survival, competitiveness, regulatory compliance, and performance sustainability. Among the most critical of these challenges are inadequate human capital development practices and limited adoption of internationally recognized food safety management systems such as ISO 22000. This research article develops an extensive theoretical and descriptive analysis that integrates human capital development, ISO 22000 implementation, and firm performance within the context of SMEs operating in the food supply chain. Drawing strictly on the provided references, the study synthesizes insights from SME policy definitions and statistics, human capital theory, firm performance measurement literature, food safety management standards, regulatory compliance frameworks, and contemporary perspectives on business consulting for SMEs.